Relation de l’incident de « l’Ever Given » dans la presse quotidienne française ; une vision du monde - Clarisse Didelon-Loiseau (Confins)
The Suez Canal was blocked by the container ship Ever Given from 23 to 29 March 2021. The incident was described in the French daily press as a global event keeping the world on edge. Based on a corpus of all toponyms quoted in the articles reporting the incident published in French daily newspapers from March 24 to April 10, 2021, the article analyses the social representations of the world space in France. It shows that, far from witnessing the emergence of the world, understood as the social space of a global society, the relation of the event highlights classical representations of globalization and of the world space structured by power relations between States.